Use of repurposed drugs in COVID-19 pandemic: Old drugs without new tricks? - Suraj Kapoor (Wolters Kluwer Medknow Publications, 2023)
Traditional drug development and discovery have not kept speed with warnings from emerging and re-emerging diseases such as Zika, Nipah, Ebola virus, MERS-CoV, and more newly the pandemic of COVID-19. The new drug discovery has a limitation of high attrition rates, substantial costs, and longer duration for discovery, so repurposing old drugs to treat the diseases becomes a popular and feasible proposition. In contrast, repurposed drugs may be beneficial for patients in a time of pandemics when the natural history of the disease remains unclear. It may be beneficial for the manufacturers as well to generate additional revenues. The use of repurposed drugs in primary care saves money as well as time, particularly important in pandemic times, which can be a cost-effective measure in the public health aspect. Review of literature was carried out about the repurposed drugs used in the COVID-19 pandemic using health bulletins, official handles of health ministries, WHO, published literature, etc. The use of repurposed drugs is beneficial, particularly in pandemic and rare diseases, but their use should be taken with due caution and thorough evaluation. Important public health aspect in primary care includes avoidance of unnecessary hoarding of such drugs. International collaboration in assessing the effectiveness of repurposed drugs is suggested.